2016
DOI: 10.17265/2161-6256/2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Method to Control Dubas Bug, Ommatissus lybicus (Deberg) (Homoptera: Tropiduchidae) in Date Palm Orchards Using Endophytic Beauveria bassiana Isolates

Abstract: Abstract:The main objective of this study was to investigate the presence of natural endophytic Beauveria bassiana within date palm tissues using molecular technique and measure their field efficacies in controlling Dubas bug, Ommatissus lybicus (Deberg). Two entomopathogenic B. bassiana isolates (MARD 108 and 100) were isolated from date palm, Phoenix dactylifera L. leaves; in addition, one isolate (MARD 92) originally from soil was identified to have endophytic property. Concentration of 1 × 10 9 conidia/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Another result of the study, when B. bassiana was applied to the soil contaminated with P. thornei at concentrations of 10 8 and 10 7 spores/ml, it was determined that the height and fresh weight of wheat plants and roots increased than the control. B. bassiana isolate (MARD 92) was identified to have endophytic property which enables it to be established within plant tissues and increases its field efficacy in controlling some pests (Khudhair et al 2016). Beserra et al (2019) reported that B. bassiana application in soybean positively affected vegetative development and reduced parasitism of P. brachyurus in roots.…”
Section: Discussionmentioning
confidence: 99%
“…Another result of the study, when B. bassiana was applied to the soil contaminated with P. thornei at concentrations of 10 8 and 10 7 spores/ml, it was determined that the height and fresh weight of wheat plants and roots increased than the control. B. bassiana isolate (MARD 92) was identified to have endophytic property which enables it to be established within plant tissues and increases its field efficacy in controlling some pests (Khudhair et al 2016). Beserra et al (2019) reported that B. bassiana application in soybean positively affected vegetative development and reduced parasitism of P. brachyurus in roots.…”
Section: Discussionmentioning
confidence: 99%
“…Target Pest Mechanism of Action Beauveria bassiana [53,54] Red palm weevil Entomopathogenic fungus Metarhizium anisopliae [55] Dubas bug Entomopathogenic fungus Bacillus thuringiensis [56] Various pests Bacterial toxins Trichogramma spp. [57,58] Date moth Egg parasitoid…”
Section: Agentmentioning
confidence: 99%